Pelaksanaan Supervisi Klinis Untuk Meningkatkan Proses Pembelajaran IPA Di Sekolah Dasar - Hamida Gusnilawati; Hadiyanto Hadiyanto (Universitas PGRI Madiun, 2021)
This research was conducted to see the performance of clinical supervision in improving the science learning process at SDN 05 Sawahan, Padang City. This research is a classroom action with the research object of the principal and teachers of SDN 05 Sawahan. Where the technique of reading data by interview, observation and documentation. The results of this study focus on clinical supposition activities carried out by the principal on teacher administration and the learning process in the classroom. This clinical supervision activity can help teachers solve problems that teachers during the classroom learning process in science learning, can motivate teachers to improve their teaching and professional skills in implementing classroom learning. Inhibiting factors based on the principal's knowledge and teacher's skills in carrying out clinical supervision in accordance with the procedures and stages of clinical supervision.